The Anterolateral Ligament is Not the Whole Story: Reconsidering the Form and Function of the Anterolateral Knee and its Contribution to Rotatory Knee Instability. Issue 4 (December 2018) - Sheean, Andrew J.; Shin, Jason; Patel, Neel K.; Lian, Jayson; Guenther, Daniel; Musahl, Volker
Abstract : The heterogeneity of available cadaveric, histologic, and radiographic results related to the anterolateral ligament (ALL) does not support its existence as a discrete anatomic structure. Moreover, focusing narrowly on the ALL in isolation, what has previously been referred to as "ALL myopia, " obscures a thorough appreciation for the stability contributions of both capsular and extracapsular structures. We consider injury to the soft tissues of the anterolateral knee–the anterolateral complex—just one component of what is frequently found to be a spectrum of pathology observed in the rotationally unstable, anterior cruciate ligament (ACL)-deficient knee. Increased lateral tibial slope, meniscal root tears, and "ramp" lesions of the medial meniscocapsular junction have all been implicated in persistent rotatory knee instability, and the restoration of rotational stability requires a stepwise approach to the assessment of each of these entities. Through an appreciation for the multifactorial nature of rotatory knee instability, surgeons will be better equipped to perform durable ACL reconstructions that maximize the likelihood of optimal clinical outcomes for patients. The purposes of this review are to provide an update on the relevant anatomy of the anterolateral knee soft tissues and to explain the multifactorial nature of rotatory knee instability in the setting of ACL deficiency.